A Gravitational Model for Estimate the Determinants of Outward Foreign Direct Investment of China - Mele, Marco; Quarto, Angelo (International Journal of Economics and Financial Issues, 2017)
Gravity models utilize the attractive force concept as an analogy to explain volume of trade or capital flows. This paper aims at proving that direct investment flows between China and a group of South-Est Asian countries are determined by standard variables included in gravity models such as: gross domestic products of home and host economy and distance between them. In our gravity model on foreign direct investment (FDI) we include not only gravity variables but also other variables that may explain what factors affecting Chinese outward foreign direct investment (OFDI): political risk, cultural proximity, the degree of openness to international trade and a proxy for natural resources. This paper, after having defined the variables that are capable of influencing Chinese OFDI, will suggest a method of econometric calculation of the gravitational model based on Prais-Winsten regression; Correlated panels corrected standard errors (PCSEs). Keywords: FDI, gravity model, Chinese OFDI JEL Classifications: F14, F15, F21